(untitled) (Siddhajyoti Interdisciplinary Journal, 2025)
Digital skill is considered as the basic skill of using digital devices for teaching and learning activities focusing on the use of MS Words, MS PowerPoints and online materials for English instruction. This study investigated the digital literacy of secondary-level English teachers of Nuwakot District, focusing on their readiness to utilize Information and Communication Technology (ICT) in English language instruction. Through a survey among 46 participants, under quantitative study, the researchers assessed the present status of digital literacy and participants’ preparedness to integrate ICT in teaching. The collected data were processed through SPSS application and further analysed through uni-varied and bi-varied tabulation. The findings suggested that teachers are in acute need of learning, updating and integrating ICT skills and online platforms to upgrade digital skills and improve day to day teaching and learning activities. The findings will further contribute to understanding the landscape of digital literacy among educators and offer valuable recommendations for improving teacher training programmes and educational technology integration in the study area.